Mental toughness and performance strategies of martial artists in practice and competition - Atefeh Beheshti; Hassan Gharayagh Zandi; Zahra Fathirezaie; Fatemeh Heidari (University of Novi Sad, Faculty of Sport and Physical Education, 2021)
This study's objective was to analyze the relationship between mental toughness and martial artists' performance strategies. Two hundred athletes (male: 105, female: 95) with an age range of 18-36 years (mean:25.12, s=4.96) who competed at university to the national standard of martial arts participated in this study. Participants answered mental toughness questionnaires and performance strategies inventory. The Pearson correlation results showed a positive and significant relationship between mental toughness and automaticity, goal-setting, imagery, self-talk, and emotional control, and a negative and significant relationship between mental toughness and attentional control in practice. Furthermore, there is a positive and significant relationship between mental toughness and activation, relaxation, self-talk, imagery, goal-setting, and emotional control in the competition. The multiple linear regression analysis results showed that goal-setting and imagery in practice and competition, self-talk in practice, and relaxation in the competition could predict mental toughness. In analyzing the subscales of mental toughness, it was concluded that tough emotions could be loaded on eight subscales of performance strategies. In the Independent-Sample T-Test, the significant differences related to gender were that men reported higher levels of self-talk (t=3.24, p<0.001), automaticity (t=2.76, p<0.006), goal-setting (t=2.63, p<0.009), imagery (t=2.18, p<0.03) and relaxation (t=2.17, p<0.03) than women.